CdtR-mediated regulation of toxin production in Clostridium difficile - Bilverstone, Terry W. (2019)
Clostridium difficile is the leading cause of hospital-associated diarrhoea in the developed world. Its pathogenicity is elicited by the production of up to three toxins: the monoglucosyltransferases TcdA and TcdB, and the ADP-ribosyltransferase, CDT. This thesis describes the generation and characterisation of twenty one chromosomally distinct mutants of C. difficile, to primarily study the genetic regulation of toxin production by the two-component system (TCS) transcriptional regulator, CdtR. R20291ΔPaLoc model strains devoid of TcdA/TcdB activity, were generated to study CDT and the cdtR gene deleted and reintegrated at the pyrE locus. The application of these strains to in vitro cytotoxicity assays developed herein, established that CdtR was required for the production of CDT to cytotoxic levels in a PCR-ribotype (RT) 027 stain. The creation of a cdtR deletion mutation in the RT 012 strain 630Δerm established that CdtR played no role in TcdA/TcdB production in this strain. Thereafter, model strains expressing (de)phosphomimetic CdtR phospho-variants were generated. Their application provided strong evidence to suggest that CdtR was activated by phosphorylation of Asp61. In contrast, the RT 078 CdtR homolog was shown to be non-functional. Nine potential TCS histidine kinase interaction partners (IPs) for CdtR, were chromosomally altered. One potential IP was identified, CdtS1, which was affected in the production of CDT, TcdA and TcdB.